Visitors, settler colonialism and aboriginal cultural heritage: Australian protected areas as transformative landscapes - Whittington, Vanessa (Critical studies in heritage, emotion and affect, 2025)
"This book analyses visitor responses to the interpretation of Aboriginal cultural heritage in Australian protected areas, focusing on Uluru-Kata Tjuta National Park in the Northern Territory and the Greater Blue Mountains World Heritage Area in New South Wales. It provides insights into the discursive features that structure various forms of interpretation of Aboriginal cultural heritage at these locales, ranging from on-site interpretative signage to audio tours available on mobile phone applications. It draws on visitors' first-hand accounts of the experience of participating in Traditional Custodian led cultural tours and camps, and the visitor learnings that resulted from these. Based on extensive interviews with visitors, the author argues that visitor responses to these experiences both perpetuate and challenge settler-colonial assumptions about Aboriginal peoples and their cultures in both more urban and remote locations. The book provides insight into the forms of interpretation that foster visitor transformations, thereby advancing a politics of reconciliation between Indigenous and non-Indigenous Australians, and the types of interpretation that may hinder such transformations, by reinforcing settler-colonial discourses and affective states. The book is aimed at students and academics attempting to develop a more critical practice in relation to heritage interpretation, tourism, Aboriginal and Torres Strait Islander cultural heritage and settler-colonialism. It will also have appeal to heritage professionals, cultural tour operators and agencies responsible for the provision of protected area interpretation, including both government sector and Indigenous organisations"-- Provided by publisher